Sequential Indirect Dual Immunohistochemistry with Primary Rabbit Antibodies on Cochlear Sections Using an Intermediate Heat‐Denaturation Step. Issue 9 (8th September 2021) - Luque, Maria; Glueckert, Rudolf
Abstract: Advanced immunohistochemical (IHC) protocols aim to visualize different molecules in situ simultaneously. These techniques are of utmost importance as a first step in studying possible interactions of proteins at the subcellular level. Colocalized stains in tissue sections indicate proximity of two proteins of interest. Frequently, double staining protocols are restricted by the lack of primary antibodies generated in different animal species for indirect IHC visualization. Here, we present a detailed protocol for mouse inner ear tissue using two different primary rabbit antibodies directed against transmembrane ion channel proteins of cochlear neurons. The two antibodies are combined for fluorescence (confocal) as well as dual multiplex colorimetric visualization in two sequential single IHC stainings. A heat‐denaturation step is performed in between. Primary antibody specificity is tested by preadsorption with the immunogenic peptide, and positive and negative tissue controls are performed to confirm the reliability of the antibody detection. We describe the whole procedure in detail beginning with tissue extraction of the mouse inner ear and continuing with chemical fixation, cryoembedding, and preparation for manual and fully automated immunostaining, including steps for heat‐induced antigen retrieval. The potential to use antibodies from the same host species for single and double IHC staining opens up multiple possibilities for detecting different targets in the same tissue section using resources and materials that are widely available. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Tissue preparation, cryoembedding, and sectioning Basic Protocol 2 : Double colorimetric immunostaining with an automatic immunostainer Basic Protocol 3 : Double manual fluorometric immunostaining with fluorescence